LITERARY GERONTOLOGY: DEFINITION, HISTORY, CONCEPTS - Gaidash, Anna (Літературний процес: методологія, імена, тенденції, 2019)
The goal of the article is to provide an extended definition and in-depth description of literary gerontology as a branch of humanities. Contemporary world witnesses how the number of elderly people increases that makes the research relevant. Literary gerontology forms in the mid-1970s in the framework of age studies. Scholars of literary gerontology examine the gerontological markers in fictional texts. Unlike sociologists or medical gerontologists who regard biological aging as involution of the body/brain and degradation of the individual, the literary scholars consider fictional representations of late adulthood in a much more contrastive and tragic focus: elderly people are forced to deal with numerous negative stereotypes of old age in a youth-oriented culture. Therefore the key concept of literary gerontology studies is ageism which etymology is traced in the lexical unit of “age”. Its initial meaning “lifetime; maturity; vital force” is lost over time, acquiring the connotation of “decline” (feebleness; senility). One of the problems of literary gerontology studies is the widespread use of ageist euphemisms in fiction. The methods used in the paper are mixed: historical data processing, analyses of interdisciplinary resources (literary gerontology, social gerontology, age studies). The results can be practical for classes of theory of literature and social gerontology. The findings of the paper inform of the origin of literary gerontolog DOI: https://doi.org/10.28925/2412-2475.2019.133